Evaluación de la pigmentación del pollo en pie a partir del empleo de la planta botón de oro (tithonia diversifolia)” - Silverio Sánchez, Luis David (2023)
In the present research, the degree of pigmentation of Broiler chickens was approached from the use of the buttercup plant (Thitonia diversifolia), in order to obtain birds and carcasses of quality, especially with an optimal pigmentation. It was carried out at "Quinta Experimental Punzara," Universidad Nacional de Loja; with a duration of 42 days, a population of 299 animals, with three treatments, T0: Control, (T1: 5%, T2: 10%), 10 repetitions for each treatment, randomly placed. The evaluated variables were the carcass yield and the carcass pigmentation. The results were analyzed using descriptive statistics and the Tukey test, which showed a statistical difference in the carcass yield variable with a (P-value 0.0423) in the treatments (5 and 10% of Thitonia diversifolia), the former reaching the best carcass percentage at 5% = 82.75%, while the lowest percentage was found in T3 at 10% = 81.44%. In addition, a significant difference was found in the pigmentation of tarsi (P-value <.0001) with the T1 control obtaining a difference with respect to the T2 5% and 10% of Thitonia diversifolia, achieving the best pigmentation. It is concluded that the use of Tithonia diversifolia 5% and 10% improves the carcass yield of Broiler chickens in 42 days, but they do not achieve a desirable pigmentation, so they must include commercial pigment. Key words: Thitonia diversifolia, Pigmentation, Performance, Diet, photocolorimetry.